Challenges of teaching of Libras as a second language to listeners - Moura, Débora Rodrigues; Palazzo, Tatiana Berchieri Miranda (Revista Hipótese, 2018)
According to Wilcox and Wilcox, teaching listeners a visual-spatial language demands research so that one can, in fact, teach the language preserving its characteristics and structure, through significant discursive practices that do not fall into what we call “signalized Portuguese”. Therefore, this work aims at discussing some challenges related to teaching LIBRAS (Língua Brasileira de Sinais) as a second language to listeners through pedagogical practices carried out with students at IFSP (Instituto Federal de Educação, Ciência e Tecnologia de São Paulo). Interviews with students who were just starting learning Libras were analysed, as well as teacher’s observations related to the learning process. The focus of the analysis was a didactic sequence involving signals, spelling and, mainly, the system inherent visual-spatial organization. From this point on, it was possible to identify some learning easiness and difficulties pointed out during the process. In general, easiness and difficulties do not rely on isolated signals, but on the visual way of structuring thought.